Performance of GACC and GACP to treat institutional wastewater: a sustainable technique - Khaleel, Mohammed R.; Ahsan, Amimul; Imteaz , Monzur Alam; El-Sergany, Moetaz M.; Nik Daud, Nik Norsyahariati; Mohamed, Thamer Ahmed; Ibrahim, Buthainah A. (Techno-Press, 2015)
Experiments were carried out using granular activated carbon (GAC) adsorption techniques to treat wastewater contaminated with organic compounds caused by diverse human activities. Two techniques were assessed: adsorbent GAC prepared from coconut shell (GACC) and adsorbent GAC from palm shell (GACP). A comparison of these two techniques was undertaken to identify ways to improve the efficiency of the treatment process. Analysis of the processed wastewater showed that with GACC the removal efficiency of biochemical oxygen demand (BOD), chemical oxygen demand (COD), turbidity, total suspended solids (TSS) and total dissolved solids (TDS) was 65, 60, 82, 82 and 8.7%, respectively, while in the case of GACP, the removal efficiency was 55, 60, 81, 91 and 22%, respectively. It can therefore be concluded that GACC is more effective than GACP for BOD removal, while GACP is better than GACC for TSS and TDS removal. It was also found that for COD and turbidity almost the same results were achieved by the two techniques. In addition, it was observed that both GACC and GACP reduced pH value to 7.9 after 24 hrs. Moreover, the optimal time period for removal of BOD and TDS was 1 hr and 3 hrs, respectively, for both techniques.